2021
DOI: 10.1038/s41598-021-92636-8
|View full text |Cite
|
Sign up to set email alerts
|

A control framework to optimize public health policies in the course of the COVID-19 pandemic

Abstract: The SARS-CoV-2 pandemic triggered substantial economic and social disruptions. Mitigation policies varied across countries based on resources, political conditions, and human behavior. In the absence of widespread vaccination able to induce herd immunity, strategies to coexist with the virus while minimizing risks of surges are paramount, which should work in parallel with reopening societies. To support these strategies, we present a predictive control system coupled with a nonlinear model able to optimize th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
(32 reference statements)
0
13
0
1
Order By: Relevance
“…The impact of COVID-19 on public health around the world has been profound. Efforts to mitigate the spread of SARS-CoV-2, the virus responsible for COVID-19 initially relied on non-pharmacological public health interventions ( 1 , 2 ), although vaccine distribution is currently increasing dramatically ( 3 ). Unfortunately, the rapid introduction of these sweeping public health measures in response to the pandemic has severely jeopardized hospital and community based breastfeeding promotion programs and continues to do so in North America ( 4 ) as well as in Europe ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of COVID-19 on public health around the world has been profound. Efforts to mitigate the spread of SARS-CoV-2, the virus responsible for COVID-19 initially relied on non-pharmacological public health interventions ( 1 , 2 ), although vaccine distribution is currently increasing dramatically ( 3 ). Unfortunately, the rapid introduction of these sweeping public health measures in response to the pandemic has severely jeopardized hospital and community based breastfeeding promotion programs and continues to do so in North America ( 4 ) as well as in Europe ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of behavioral restrictions is changed based on the number of isolated symptomatically infected persons and its trend of increasing or decreasing . Pataro et al [ 50 ] introduced a framework for optimizing the required levels of public health policies and referred to the importance of finely tuning the level of restriction on the population’s mobility. In this study, we assume that the intensity of the intervention, such as behavioral restrictions, can be divided into, at most, four levels.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these NPI were lifted over time following declines in number of cases and deaths between each infection wave. Several studies reported the effects of NPIs on the incidence of COVID-19 21,25,26 , highlighting how, coupled with human mobility patterns, they can be applied to gauge the intensity of government stringency needed to achieve control of viral transmission rates 28 . The governmental decrees that have been issued during this period can be extracted from state-and federal-level Official Bulletins (in Portuguese, Diário Oficial).…”
Section: Non-pharmaceutical Interventionsmentioning
confidence: 99%